Optimalisasi Media Sosial untuk Dakwah Islam: Tantangan dan Strategi: Optimizing Social Media for Islamic Da'wah: Challenges and Strategies - Ridwan, Ridwan; Ramsiah Tasruddin (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
This study aims to identify the primary challenges faced by Islamic preachers in utilizing social media as a medium for da'wah and to analyze the strategies employed to effectively convey Islamic messages. A qualitative approach with a descriptive-analytical method was employed in this research. The findings reveal that social media offers vast opportunities to reach a broad audience without geographical constraints, yet it also presents challenges requiring creativity, knowledge, and high moral standards. To address these challenges, preachers must enhance digital literacy, communication skills, and leverage community support. The study recommends developing digital technology training for preachers and strengthening collaborative efforts within da'wah communities.